The emergence of microbiological inputs and the challenging laboratorisation of agriculture: lessons from Brazil and Mexico - Goulet, Frédéric; Fonteyne, Simon; Lopez-Ridaura, Santiago; Niederle, Paulo; Odjo, Sylvanus; Schneider, Sergio; Verhulst, Nele; Van Loon, Jelle (Springer, 2025)
In this article, we analyse the tensions associated with the emergence of microorganism-based agricultural inputs in two Latin American countries, Brazil and Mexico. More specifically, we examine the ways in which these technologies, which are based on the use of living organisms, leave public microbiology research laboratories and are further developed by manufacturers or farmers. To this end, we draw on the concept of the ‘laboratorisation’ of society, part of the actor-network theory. We show that the emergence of these technologies is currently facing a number of challenges, due to the risks associated with their biological nature and the difficulty involved in establishing production processes as reliable as those used in reference laboratories. Whether produced by companies or on farms, the quality and safety of the practices and of these products are the subject of debate, as well as the focus of scientific, economic and political scrutiny. These microbiological inputs are evidence for the transformation of the relationship between science, industry, users and politics that is taking place around the emergence of alternatives to synthetic chemical inputs in agriculture, and more broadly, about the use of microbiological resources in agriculture.